2002
DOI: 10.1046/j.1365-2117.2002.00182.x
|View full text |Cite
|
Sign up to set email alerts
|

Mid‐Palaeocene palaeogeography of the eastern North Sea basin: integrating geological evidence and 3D geodynamic modelling

Abstract: The Mid‐Palaeocene palaeogeography of Denmark and the surrounding areas have been reconstructed on the basis of published geological data integrated with 3D geodynamic modelling. The use of numerical modelling enables quantitative testing of scenarios based on geological input alone and thus helps constrain likely palaeo‐water depths in areas where the geological data are inconclusive or incomplete. The interpretation of large‐scale erosional valleys and small‐scale circular depressions at the Mid‐Palaeocene T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 55 publications
0
27
0
Order By: Relevance
“…In the eastern North Sea the Paleocene sand-filled Siri Canyon is associated with sand injections observed on core and seismic scale (Hamberg et al, 2007;Svendsen et al, 2010). Other fluid flow features in the central North Sea includes pockmarks and gas chimneys (Heggland, 1998;Gemmer et al, 2002). The features observed in the case studies from the North Sea include Late Cretaceous, Oligocene and Miocene sediment intrusions and extrusions, and Oligocene and Miocene pockmarks (Fig.…”
Section: Introductionmentioning
confidence: 90%
“…In the eastern North Sea the Paleocene sand-filled Siri Canyon is associated with sand injections observed on core and seismic scale (Hamberg et al, 2007;Svendsen et al, 2010). Other fluid flow features in the central North Sea includes pockmarks and gas chimneys (Heggland, 1998;Gemmer et al, 2002). The features observed in the case studies from the North Sea include Late Cretaceous, Oligocene and Miocene sediment intrusions and extrusions, and Oligocene and Miocene pockmarks (Fig.…”
Section: Introductionmentioning
confidence: 90%
“…This topography probably coincided with the Shetland Platform and the present-day Norwegian mainland. Some topography was probably also generated along the late Cretaceous and early Paleogene inversion zones (Ziegler 1990;Gemmer et al 2002). The elevation and relief of the topography of southern Norway and Shetland is difficult to constrain because of the absence of late Mesozoic and Cenozoic sediments, but a maximum elevation of the order of a few hundred metres above (palaeo-) sea level, gently sloping towards the shoreline with only minor local relief seems plausible.…”
Section: Rationalementioning
confidence: 97%
“…They occur predominantly in fine-grained siliciclastic depositional settings, although a few case studies have been reported in carbonate settings (Gemmer et al, 2002;Judd and Hovland, 2007;Betzler et al, 2011). Seafloor depressions of variable sizes are also known to form from the expulsion of fluidized sediments from depth and the subsequent collapse of the overburden (e.g., Davies, 2003).…”
Section: Introductionmentioning
confidence: 97%